PENINGKATAN AKTIVITAS PEMBELAJARAN PKNMODEL KOOPERATIFTEKNIK SNOWBALL THROWING PADA PESERTA DIDIK KELAS 1V SD - Martie Dewi Wahyuni; Mastar Asran; Rosnita Rosnita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2018)
AbstractThis research entitled Enhancement of Learning Activity of Citizenship Education with Cooperative Model of Snowball Throwing Technique on 4th Grade Student of State Elementary School 16 Rasau Jaya. The purpose of this research is to describe the use of cooperative model of Snowball Throwing technique to improve the learning activity of Civics in class IV public elementary school 16 Rasau Jaya . The method used in this research is descriptive with the form of classroom action research assessment, observation data collection techniques with data collection tool in the form of observation sheet. Implemented in 3 cycles, each cycle there is an increase in the ability of teachers in learning melakasanakan on the first cycle of 2.01, cycle II to 3.01, and cycle III 3.9. Increased physical activity of cycle I was 58,33%, cycle II to 79,16%, and cycle III 95,83%. The mental activity of cycle I is 56,25%, cycle II becomes 77,67%, and cycle III 92,7%. Emotional activity of cycle I is 62,5%, cycle II becomes 77,67%, and cycle III 100%. Keywords: Improved Learning Activity, Cooperative Model, Snowball Throwing ……………Technique